Contingency, behavioural and evolutionary perspectives on public and non-profit governance - Gnan, Luca.; Hinna, Alessandro; Monteduro, Fabio (Bingley, U.K. : Emerald, 2015)
This volume assesses governance in public and non-profit organizations. Building on and challenging recent research in this area, this volume critically examines the contextual, behavioural and historical factors of governance. Topics include; the role, behaviour and effectiveness of a board of directors; the relationships between board members and stakeholders; innovations in governance; accountability, transparency and integrity of governance; measuring and assessing organizational performance and new forms of governance arrangements in service provision.
Managing paradoxes in governance : tensions in the emergence of a new board / Linda Ho<U+0308>glund, Mikael Holmgren Caicedo, Maria Ma<U+030a>rtensson -- Exploring antecedents and impact of board effectiveness in clean-tech enterprises / Ekaterina S. Bjornali, Andreas Ellingsen -- Thou shall not meddle : exploring autonomy in the board-executive director relationship / Gregory Bott -- Who cares about public interests? A casebased analysis of the role of boards, in Dutch semipublic organizations / Hans van Ees ... [et al.] -- Defining hybridity and hybrid contingencies in public organizations : an alternative conceptual model / Lode De Waele, Liselore Berghman, Paul Matthyssens -- Political pressures : too large, too small, or just right? / Patricio Rojas -- An anatomy of governance failures in municipal bankruptcy / Enrico Guarini, Anna De Toni, Cinzia Vallone -- Leadership in local government organizations in Lithuania and Germany / Irma Rybnikova ... [et al.] -- Participatory governance in the networks of stakeholders : expression of collective identity / Birute<U+0307> Mikulskiene<U+0307> -- Governance learning : building a network around managerial innovations / Chloe<U+0301> Vitry, Eduardo Chia.
Print version record
Keywords: Political Science -- Public Affairs & Administration; Public administration; Corporate governance; Nonprofit organizations -- Management; Public administration